Creating a Revolutionary Academic Program. - RAMACHANDRAN, UMAKISHORE; GALIL, ZVI (Communications of the ACM, 2022)
The article focuses on the creation of the Georgia Tech (GT) Online Master's in Computer Science (OMSCS) program. Topics include the supply and demand for skilled information technology (IT) professionals with a graduate degree in computer science (CS) and how the program is based on massive open online course (MOOC) technology.